Amphidromic Lines in the Atmosphere: An Example of Global Pressure Field Annual Harmonic. Issue 4 (28th April 2021) - Zhao, Enjin; Mu, Lin; Jiang, Haoyu
Abstract: Amphidrome refers to an oceanic point where the amplitude of one harmonic constituent of the tidal system is zero, and the phase of the harmonic constituent is undetermined. The concept of amphidrome can also be used in climatological studies because of the existence of annual amphidromes, points of zero amplitude, and ill‐defined phase of annual cycle. This study investigated the global atmospheric geopotential height from the ERA‐interim to identify annual amphidromes at different isobaric altitudes. Many well‐defined annual amphidromes were identified. These amphidromic points appear always as twins with different rotating directions with respect to phases. This phenomenon can be explained mathematically with the basic theory of spherical algebraic topology, suggesting amphidrome twins as a common feature for periodic variables in the atmosphere. Due to the spatial continuity of atmospheric parameters, amphidromes at different isobaric altitudes can be concatenated into amphidromic lines. Amphidromic lines have a three‐dimensional structure with both clockwise and anticlockwise vertical branches connected by one or two horizontal components. Particularly, some amphidromic lines in the atmosphere can be closed loops when they are connected by two horizontal components. The rotary phases around the amphidromic loops are similar to the magnetic induction lines around a closed electromagnetic coil. Plain Language Summary: Amphidrome refers to an oceanic point that is encircled by one harmonic constituent of rotary tides. The amplitude of the amphidromic point is zero and its phase is undetermined. Recent studies showed that an amphidrome is not a tide‐only phenomenon but widely exists in oceanic and atmospheric systems. This study investigated annual amphidromes in the atmospheric pressure field. Many well‐defined amphidromic points can be found at different heights, and four interesting features of these amphidromes were identified: (1) Amphidromes are very common in many periodic atmosphere features and always appear in pairs of two amphidromes that rotate in opposite directions, termed amphidromic twins. (2) The location of amphidromes in different layers changes slowly with height forming so‐called amphidromic lines. (3) Amphidromic lines have a three‐dimensional (3D) structure with both clockwise and anticlockwise vertical branches, connected by one or two horizontal components. The amphidromic twins are, in fact, only two vertical branches. (4) The 3D structure of specific amphidromic lines, sometimes, can be a closed loop named amphidromic loop. The phase rotating around this loop is similar to magnetic induction lines around a closed electromagnetic coil. Key Points: Amphidromes for periodic variables in the atmosphere are a common feature and always appear as twins with opposite rotating directions Amphidromes at different heights form amphidromic lines with cyclone and anticyclone branches, connected by one or two horizontal components The three‐dimensional structure of amphidromic lines in the atmosphere can sometimes be a closed loop